1996
DOI: 10.1074/jbc.271.13.7529
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Expression and Dietary Regulation of Chimeric Mitochondrial 3-Hydroxy-3-methylglutaryl Coenzyme A Synthase/Human Growth Hormone Gene in Transgenic Mice

Abstract: We have studied the role of the mitochondrial 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) synthase gene in regulating ketogenesis. The gene exhibits expression in various tissues and it is regulated in a tissue-specific manner. To investigate the underlying mechanisms of this expression, we linked a 1148-base-pair portion of the mitochondrial HMG-CoA synthase promoter to the human growth hormone (hGH) gene and analyzed the expression of the hGH reporter gene in transgenic mice. mRNA levels of hGH were observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…displaying constant mHMGCoA synthase mRNA concentrations in the colonic epithelium over a 2‐day period of fasting, characterized by profound changes in plasma insulin and glucagon concentrations. This result confirms that the expression of the mHMGCoA synthase in the colon and in the liver is differentially regulated [29].…”
Section: Discussionsupporting
confidence: 83%
“…displaying constant mHMGCoA synthase mRNA concentrations in the colonic epithelium over a 2‐day period of fasting, characterized by profound changes in plasma insulin and glucagon concentrations. This result confirms that the expression of the mHMGCoA synthase in the colon and in the liver is differentially regulated [29].…”
Section: Discussionsupporting
confidence: 83%
“…The occurrence of a nuclear receptor responsive element (NRRE), which binds peroxisome-proliferator-activated receptor (PPAR), chicken ovalbumin upstream promoter transcription factor (COUP-TF) and hepatocyte nuclear factor-4 (HNF-4), has been demonstrated (see below) [11,81,82], in addition to the cAMP regulatory element (CRE) binding site (A. Eckers, C. Caudevilla, G. Asins, F. G. Hegardt and D. Serra, unpublished work). Some of these sequences present in the rat gene are also observed in the human [80] and pig [83] mitochondrial HMG-CoA synthase gene 5h flanking regions.…”
Section: Isolation Of Mitochondrial Hmg-coa Synthase Genesmentioning
confidence: 90%
“…Comparison of this 5h flanking region with the canonical sequences of several cis elements shows that several known sequences appear in this 5h flanking region (Table 1). Transfection studies in HepG2 cells [7] and in transgenic mice [80] suggest multi-hormonal regulation of gene transcription. The occurrence of a nuclear receptor responsive element (NRRE), which binds peroxisome-proliferator-activated receptor (PPAR), chicken ovalbumin upstream promoter transcription factor (COUP-TF) and hepatocyte nuclear factor-4 (HNF-4), has been demonstrated (see below) [11,81,82], in addition to the cAMP regulatory element (CRE) binding site (A. Eckers, C. Caudevilla, G. Asins, F. G. Hegardt and D. Serra, unpublished work).…”
Section: Isolation Of Mitochondrial Hmg-coa Synthase Genesmentioning
confidence: 99%
“…To explore the control of the HMGCS2 gene, we examined its transcriptional regulation. Transient transfection experiments and testing of transgenic mice have revealed that a 1149 bp fragment of the 5h-flanking region contains the elements responsible for the multi-hormonal regulation of transcription of this gene [10,11]. The HMGCS2 gene promoter contains a peroxisome proliferator-activated receptor-responsive element, and the activation of HMGCS2 gene expression by fatty acids may be mediated by this receptor [12].…”
Section: Introductionmentioning
confidence: 99%